2009
DOI: 10.1080/15538360903378559
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Regional Portuguese Apple Cultivars in Different Harvest Years

Abstract: In the present study, apples of regional cultivars originating from Portugal were compared in terms of some chemical properties during three consecutive harvest years. It was possible to conclude that these regional cultivars of apples were generally sweeter and contained more minerals than other cultivars described in the literature. The data revealed that the acid, protein, and mineral content depended on the apple cultivar. The acid content varied notably with the 2004, 2005, and 2006 harvests. For total s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
1
0
0
2
Order By: Relevance
“…The chemical composition of the discarded apples used in this study is similar to that reported for commercialized regional Portuguese apple cultivars, 36 showing high total sugar content and low fibre and protein concentrations. As expected, fibre and protein contents of cowpea stover were high and within the range of values reported by Savadogo et al 37 and Gonçalves et al 7 Furthermore, chemical composition values of cowpea stover are within the general range of values described for legume straws.…”
Section: Discussionsupporting
confidence: 78%
“…The chemical composition of the discarded apples used in this study is similar to that reported for commercialized regional Portuguese apple cultivars, 36 showing high total sugar content and low fibre and protein concentrations. As expected, fibre and protein contents of cowpea stover were high and within the range of values reported by Savadogo et al 37 and Gonçalves et al 7 Furthermore, chemical composition values of cowpea stover are within the general range of values described for legume straws.…”
Section: Discussionsupporting
confidence: 78%
“…Średnia zawartość suchej masy w świeżych jabłkach wyniosła 12,39 g/100 g produktu, co jest zbliżone do wyników badań Guiné i wsp. [18] (15 ÷ 20 g/100 g produktu). Po zastosowaniu procesów utrwalania owoców zawartość suchej masy wynosiła odpowiednio: 12,89 g/100 g jabłek zamrażanych, 88,77 g/100 g jabłek suszonych konwekcyjnie oraz 96,27 g/100 g jabłek liofilizowanych.…”
Section: Wyniki I Dyskusjaunclassified
“…Jabłka niepoddane procesom utrwalaniu zawierały znacznie więcej białka niż jabłka badane przez Krishnę [21] (0,26 g/100 g świeżej masy) oraz Guiné i wsp. [18] (1,59 g/100 g suchej masy). Proces zamrażania nie miał istotnego wpływu na ilość białka w jabłkach (p > 0,05).…”
Section: Wyniki I Dyskusjaunclassified